Theoretical framework and methodological concepts of design culture - Y. O. Butsykina, (Ukrainian Cultural Studies, 2017)
The article is devoted to introducing new theoretical frameworks and methodological concepts from the field known as science and technology studies (STS) and discussing their potential for design history. The concepts of design and culture are analyzed and compared within the article, providing the possibility of developing the complex concept of “design culture”. The study shows that design can be considered as a social and cultural phenomenon, that design historians may find that the sociology and the history of technology can provide an appropriate theoretical framework and methodological repertoire for studying design, not only as the part of art history. The article introduces main concepts from science and technology studies that might be of particular value to design history and culture, focusing on actor-network theory, script analysis and domestication.
Keywords: design, design culture, design history, art history, actor-network theory, script analysis, domestication